2017
DOI: 10.1108/ijchm-12-2015-0694
|View full text |Cite
|
Sign up to set email alerts
|

The determinants of hotel room rates: an analysis of the hotel industry in Warsaw, Poland

Abstract: Purpose This study aims to measure the effect on prices through the differing characteristics and attributes of hotels. Design/methodology/approach A hedonic price model (HPM) was adopted to estimate the impact of various site and situational factors on hotel prices in Warsaw, Poland. To better understand room rates not explained by HPM, spatial analysis of residuals was used. Datasets regarding prices from three different online travel agents (OTAs) and star ratings, either official or provided by OTAs, wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(38 citation statements)
references
References 37 publications
3
33
0
2
Order By: Relevance
“…Thus, city centre is the most impactful place creating hotel spatial clusters. This was confirmed by Napierała and Leśniewska (2015), Pawlicz and Napierała (2017), Shoval (2006), and Shoval and Cohen-Hattab (2001) who investigated the impact of distance from the city centre, or location in central district of the city, on hotel room rates. The authors used both quantitative and qualitative methods and found that location in a city centre allows hoteliers to offer their services at higher prices.…”
Section: Agglomeration Effect Of Intra-urban Location Of Hotelsmentioning
confidence: 68%
“…Thus, city centre is the most impactful place creating hotel spatial clusters. This was confirmed by Napierała and Leśniewska (2015), Pawlicz and Napierała (2017), Shoval (2006), and Shoval and Cohen-Hattab (2001) who investigated the impact of distance from the city centre, or location in central district of the city, on hotel room rates. The authors used both quantitative and qualitative methods and found that location in a city centre allows hoteliers to offer their services at higher prices.…”
Section: Agglomeration Effect Of Intra-urban Location Of Hotelsmentioning
confidence: 68%
“…Revenue management research has drawn attention in recent decades from scholars and professionals focused on areas such as RM uses, processes, and structures. There has been a rise in RM models such as the hedonic price model for measuring the impacts of various factors on hotel prices [17], the successive consumer decision procedures model [18], dynamic and deterministic programming models, used to manage matters of RM in hotels [19], RM implementation and strategy models [10], the choice model [20], the room intensification integrated model for hotel proceeds [21], forecasting models [22], and the multinomial logit model for RM [23].…”
Section: Practices Of Revenue Management In Hotelsmentioning
confidence: 99%
“…Similarly, models developed for pricing incorporate some notion of external conditions, e.g. weather or politics [20] and hotel characteristics like location and star rating [21]. The approach proposed in [22] is worth to mention as the authors use not only nonlinear model but also employ automatic feature selection to introduce additional variables.…”
Section: Related Workmentioning
confidence: 99%